A wicked problem: Systemic issues surrounding Canadian equestrian dressage and dressage horse welfare - Megan Ross; Kathryn Proudfoot; Katrina Merkies; Charlotte Lundgren; Caroline Ritter (Animal Welfare)
Competitive dressage’s social licence to operate is in jeopardy due to ethical concerns surrounding the use of horses for dressage. There is limited research that contributes to our understanding of Canadian equestrian perspectives on the use of horses in dressage. The objectives of this study were to: (1) explore the cultural context of the Canadian dressage industry, including how horse well-being is integrated within the culture; and (2) investigate coaches’ and riders’ perceptions and experiences with the use of horses for dressage. An ethnographic case study approach was employed, where MR spent 2–6 weeks with each of the four participating Equestrian Canada Certified dressage coaches and their riders (at least four riders per coach for a total of 19 riders). Data collection included direct observation, recording field notes and conducting at least one in-depth interview with each coach and rider. Interviews and field notes were analysed using reflexive thematic analysis leading to the development of three themes: (1) the systems that participants operate within; (2) how these systems foster a culture of contradiction in the industry; and (3) the ‘equestrian dilemma’ highlighting how participants navigate their love for horses with their horses’ well-being amid the sport’s demands. The three themes portray that the issues faced by the dressage industry may be rooted in systemic problems and could be described as a ‘wicked problem’. These results aim to inform future research initiatives that promote a holistic understanding of the challenges faced by the dressage industry and promote systems thinking solutions.